Cottage Food in Florida - Sarah M. Ellis; Jennifer Hagen; Matthew D. Krug (EDIS)
In Florida, individuals can manufacture, sell, and store specific types of cottage food products in their primary home kitchen in accordance with Florida Statute 500.80. This new 3-page fact sheet, written by Sarah M. Ellis, Jennifer Hagen, and Matthew D. Krug and published by the UF/IFAS Food Science and Human Nutrition Department, provides basic information and resources for clientele who are interested in starting a food-based business out of their home kitchen. This document is one in a "Florida Food Entrepreneur" series, which seeks to assist new and established food entrepreneurs by providing information on topics relevant to food-based businesses. https://edis.ifas.ufl.edu/fs425